Obstetric and neonatal outcomes among pregnancies with hepatitis E infection - Hiralal Pardeshi, Sachin; Mayadeo, Niranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Maternal mortality is an important health indicator. Hepatitis E is a common viral infection affecting pregnant women. The maternal morbidity and mortality relating to this infection is not extensively reported and deserves to be studied. Methods: A retrospective study was conducted in a tertiary care referral centre and the obstetric and neonatal outcomes among patients with hepatitis E infection were studied for duration of 1 year. Results: Among 24 patients, there were 7 mortalities. Majorities were primigravidae and presented during third trimester. A sizeable number required blood transfusions and ICU stay. 7 were stillbirths and majorities were low birth weight babies. Conclusions: Hepatitis E causes significant maternal and neonatal morbidity.